GP-DEMO: Differential Evolution for Multiobjective Optimization based on Gaussian Process models - Mlakar, Miha; Petelin, Dejan; Tušar, Tea; Filipič, Bogdan (European journal of operational research, 2015)
•New surrogate-model-based evolutionary multiobjective algorithm GP-DEMO is proposed.•New relations for comparing solutions under uncertainty are defined.•Comparing solutions under uncertainty prevents wrongly performed comparisons.•GP-DEMO in comparison to DEMO obtained similar results with less exact evaluations. This paper proposes a novel surrogate-model-based multiobjective evolutionary algorithm called Differential Evolution for Multiobjective Optimization based on Gaussian Process models (GP-DEMO). The algorithm is based on the newly defined relations for comparing solutions under uncertainty. These relations minimize the possibility of wrongly performed comparisons of solutions due to inaccurate surrogate model approximations. The GP-DEMO algorithm was tested on several benchmark problems and two computationally expensive real-world problems. To be able to assess the results we compared them with another surrogate-model-based algorithm called Generational Evolution Control (GEC) and with the Differential Evolution for Multiobjective Optimization (DEMO). The quality of the results obtained with GP-DEMO was similar to the results obtained with DEMO, but with significantly fewer exactly evaluated solutions during the optimization process. The quality of the results obtained with GEC was lower compared to the quality gained with GP-DEMO and DEMO, mainly due to wrongly performed comparisons of the inaccurately approximated solutions.